Intraoperative femoral rotational kinematics are similar in varus and valgus knees during medial pivot total knee arthroplasty. (January 2023) - Yamagami, Ryota; Inui, Hiroshi; Taketomi, Shuji; Kono, Kenichi; Kawaguchi, Kohei; Sameshima, Shin; Kage, Tomofumi; Arakawa, Takahiro; Tanaka, Sakae
Abstract: Background: Medial-pivot type total knee arthroplasty is designed to reproduce physiological femoral rotational kinematics during knee flexion; however, its rotational kinematics in valgus knees remain unknown. This study's hypothesis is that its kinematics show the similar medial pivot motion in valgus knees as in varus knees. Methods: This retrospective study included 50 cases of primary medial-pivot type total knee arthroplasty performed with navigation for knee osteoarthritis. Cases were grouped as valgus ( n = 20) or varus ( n = 30). In valgus knees, surgeons used preoperative manual testing to confirm that alignment was correctable. They evaluated femoral rotational kinematics at maximum extension, 30°, 60°, 90°, and maximum flexion, using a navigation system, both before and after implantation. Finally, intraoperative rotational kinematics, postoperative patient-reported outcomes, and knee range of motion were compared between the two groups. Findings: Before implantation, both valgus and varus knees displayed external femoral rotation relative to the tibia during knee flexion. The rotation magnitude was significantly larger in varus knees at 60°, 90°, and maximum flexion angles compared to valgus knees ( P < 0.05). In contrast, after implantation, both groups displayed external femoral rotation of 12–13° during knee flexion with no significant differences between the two groups at any knee flexion angle tested ( P > 0.05). Short-term clinical outcomes were comparable between valgus and varus knees. Interpretation: Postoperatively, medial-pivot type total knee arthroplasty for knee osteoarthritis resulted in external femoral rotation during knee flexion. Notably, this occurred even in valgus knees with good short-term clinical outcomes. Highlights: We evaluated femoral rotational kinematics of medial-pivot total knee arthroplasty. Varus ( n = 30) and valgus ( n = 20) knees were compared. Before implantation, both groups exhibited different kinematics pattern. Conversely, after implantation, both exhibited similar femoral rotational patterns. Moreover, clinical outcomes of valgus knees were comparable to varus knees.